Implementation of Maqāṣid Sharia in Islamic Financial Management: Evidence From PT Bank Nano Syariah - Muhammad Khoirul Fikri; Dliya’udin Achmad; Zohaib Hassan Sain (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose: This study aims to analyze the implementation of maqasid sharia in Islamic financial management at PT Bank Nano Syariah. The bank represents a medium-sized Islamic financial institution that is strengthening its institutional structure and economic strategy.Design/Methodology: This research employs a qualitative case study approach using in-depth interviews, participatory observation, and internal document analysis. The study involved eight informants and was conducted throughout 2025. Interview data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The analysis was conducted through thematic coding based on the principles of maqāṣid sharia, supported by triangulation of sources and research methods.Findings: The findings reveal that PT Bank Nano Syariah comprehensively internalizes the principles of maqāṣid sharia in financial planning, budgeting, risk management, financing, and performance evaluation. The principle of hifz al-din is implemented through compliance with DSN-MUI fatwas, sharia verification processes, and sharia financial literacy programs. The principle of hifz al-mal is reflected in risk management strategies, customer asset protection, and digital transaction security. Meanwhile, hifz al-nafs and hifz al-aql are implemented through microfinance programs aimed at community economic empowerment and financial literacy education. The principle of hifz al-nasl is realized through education financing and family business support programs that emphasize generational sustainability. These findings confirm that maqāṣid sharia functions not only as a normative principle but also as an operational managerial framework in Islamic financial management.Practical Implications: This research provides practical implications for strengthening maqasid-based Islamic banking policies and offers empirical insights into the internal practices of small- and medium-sized Islamic banks.Originality/Value: The novelty of this research lies in demonstrating how maqāṣid sharia can be operationalized in the internal financial management practices of small- and medium-sized Islamic banks